Languages of Communication in Baghdad: Domains and Perceptions - Dweik, Prof. Bader S.; Al-Rahal, Sara N. (JOURNAL OF ADVANCES IN LINGUISTICS, 2016)
The purpose of this study is to investigate the domains of use of the Turkmen language and Arabic in Baghdad and to explore attitudes towards Turkmen and Arabic. A sample, comprising (100) subjects from the Turkmen of Baghdad, is selected purposefully to fill out a sociolinguistic questionnaire to solicit information about the participants’ demographic background, language use in different contexts and language attitudes towards the ethnic language, Turkmen and the mainstream language, Arabic. The results have revealed that the Turkmen of Baghdad use their ethnic language in different domains especially at home and among the family members. Also, they use both languages (their ethnic language and Arabic) in different social domains such as neighborhood, place of work, schools, media and other public places and have displayed positive attitudes towards Turkmen and Arabic alike.